DEVELOPMENT OF THE METHODS OF COMMERCIALIZATION OF INNOVATION IN UKRAINE - Khomenko, L.M.; Saher, L. Yu. (Socio-economic relations in the digital society, 2022)
Innovations contribute to producing products with new or improved characteristics, providing better services that best meet human needs. However, it is necessary not only to develop innovation but also to commercialize it. During commercialization, Ukrainian enterprises face political and economic problems, social instability, economic stagnation, lack of established practice of marketing research to understand market needs, financial problems in finding investors, and more. There are currently some methods for commercializing innovation. All of them are developing differently in Ukraine. Scientific interest in the commercialization of innovations is growing every year. Thus, there were found more than 2700 publications on the commercialization of the innovation in the Web of Science database, half of which have been published in the last five years. The work aims to study the development of some commercialization methods of innovations in Ukraine. The study was conducted based on the State Statistics Service of Ukraine reports. The number of innovation-active enterprises and enterprises that implemented innovations in 2019 has halved (compared to 2010). At the same time, the number of enterprises that implemented innovations is 12-13% less than that of innovation-active industrial enterprises. The number of new technological processes introduced into production of industrial enterprises increased by 13%, and the number of introduced innovative products decreased by 11%. Expenditure on the innovation of industrial enterprises increased by 75%, and the volume of sold innovative industrial products increased by only 1%. The number of cooperatives in 2022 decreased by 13% (compared to 2013). The number of franchisors in 2020 increased by 42% (compared to 2010). The number of companies providing financial leasing services in Ukraine during 2015-2019 decreased by 42%. The domestic engineering market remains in its infancy but has considerable room for introducing international practice in the implementation of engineering projects. In general, since 2016, franchising and cooperation have been growing, among other ways of commercializing innovations, declining.
Keywords: technology transfer; commercialization; innovation; franchising; leasing; engineering; cooperation